PENGARUH EFEKTIVITAS PENDIDIKAN KEWIRAUSAHAAN TERHADAP KESIAPAN BERWIRAUSAHA SISWA DIMEDIASI EFEKTIVITAS MODEL PEMBELAJARAN TEACHING FACTORY : Survei pada Siswa Kelas XI Program Keahlian Bisnis Daring dan Pemasaran di SMK se-Kota Subang - Meilita Nur Hasanah, - (2023)
This research is motivated by the low readiness for entrepreneurship among SMK students. This study aims to identify and analyze the role of the teaching factory learning model in mediating the influence of entrepreneurship education on entrepreneurial readiness. The population in this study were class XI students in the online business and marketing expertise program with a total of 300 and a sample size of 100 at SMKs throughout Subang City. The research method used in this research is descriptive and verification with the data analysis technique used is the measurement model test (outer model) and the structural model test (inner model). The results of this study indicate that entrepreneurship education has an effect but not significant on entrepreneurship readiness, entrepreneurship education has a significant and significant effect on the teaching factory learning model, the teaching factory learning model has a significant and significant effect on entrepreneurship readiness, and the teaching factory learning model mediates the effect of entrepreneurship education on student entrepreneurship readiness.